1979
DOI: 10.1159/000275429
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometry in 2-Year-Old Children

Abstract: Repetitive screening tympanometry performed in 240 healthy 2-year-old children showed that tympanometric conditions are significantly better in the summer season than in the spring or winter. A very large tendency to spontaneous normalization of the tympanogram type B was demonstrated. Only 16% of the ears that had type B at the first investigation in November had the same type in August. Simultaneous with the normalization of some ears others deteriorated, thus in November type B tympanogram was found in 12%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 3 publications
0
15
2
1
Order By: Relevance
“…(21,26) According to Tos et al, gender difference in otitis media represents mainly the influence of cultural factors. (27) In our study, children with OME had larger number of family members in household than normal children (p= <0.0001). From multivariate regression model, we found that family size of more than 4 members is one of the strongest predictors of OME (OR= 4.192, 95% CI: 2.033-8.643).…”
Section: Discussionmentioning
confidence: 43%
“…(21,26) According to Tos et al, gender difference in otitis media represents mainly the influence of cultural factors. (27) In our study, children with OME had larger number of family members in household than normal children (p= <0.0001). From multivariate regression model, we found that family size of more than 4 members is one of the strongest predictors of OME (OR= 4.192, 95% CI: 2.033-8.643).…”
Section: Discussionmentioning
confidence: 43%
“…Unfortunately, the close physical contact among children in day-care favors the transmission of infectious diseases. Previous studies have focused mainly on the risk of upper respiratory tract infection (URTI) and otitis media, which are reported to occur two to three times more frequently in children attending day-care centres (DCCs) than in those cared for at home [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is particularly impor tant because evidence suggests that frequent episodes (es pecially of otitis media) may adversely affect neurocognitive and language development [8] and lead to numerous medical and surgical treatments [9]. Several studies in Scandinavia [3,4,10] showed that the prevalence of abnormal tympanograms ranged from 5 to 8% in children at home or attending family day care, respectively, com pared to 24% in children attending DCCs.…”
Section: Introductionmentioning
confidence: 99%
“…8,56,57 In truth, the prevalence of negative pressure in the middle ear and Type B tympanograms, indicative of effusion in the middle ear, are greater in children cared for in day care centers with many others; intermediate in children cared for in family homes with fewer companions and less still in children cared for at home. 58,59 In the meta-analysis of Uhari et al, the risk of AOM also increased with child care outside the home (RR 2.45; 95%CI 1.51-3.98) and although on a lower scale, also with care in family homes (RR 1.59; 95%CI 1.19-2.13). 60 It is postulated that the risk is proportional to the number of companions the child is in contact with.…”
Section: Day Care Center Attendancementioning
confidence: 98%